Recent Advances in Heterogeneous Ir Complex Catalysts for Aromatic C–H Borylation - Maeda, Kyogo; Motokura, Ken (Synthesis, 2021)
Aromatic C–H borylation catalyzed by an Ir complex is among the most powerful methods for activating inert bonds. The products, i.e., arylboronic acids and their esters, are usable chemicals for the Suzuki–Miyaura cross-coupling reaction, and significant effort has been directed toward the development of homogeneous catalysis chemistry. In this short review, we present a recent overview of current heterogeneous Ir-complex catalyst developments for aromatic C–H borylation. Not only have Ir complexes been immobilized on support surfaces with phosphine and bipyridine ligands, but Ir complexes incorporated within solid materials have also been developed as highly active and reusable heterogeneous Ir catalysts. Their catalytic activities and stabilities strongly depend on their surface structures, including linker length and ligand structure.1 Introduction and Homogeneous Ir Catalysis2 Heterogeneous Ir Complex Catalysts for C–H Borylation Reactions3 Other Heterogeneous Metal Complex Catalysts for C–H Borylation Reactions4 Summary and Outlook
Keywords: C–H borylation; Ir complex; heterogeneous catalyst; supported catalyst; bipyridine ligand